Chemistry at the rim: Differentiation of isomeric open-cage fullerenes by MALDI-LIFT and ESI-MS/MS - Nye, Leanne C.; Hitzenberger, Jakob; Roubelakis, Manolis M.; Orfanopoulos, Michael; Drewello, Thomas (International Journal of Mass Spectrometry, 2019)
Isomeric open-cage fullerenes ( OCFs) are studied by MALDI-LIFT. The two types of isomers feature different connectivities of the heteroatoms at the rim of the orifice to the fullerene cage. The molecular ions (radical cations, M+.) are generated by electron transfer MALDI, using DCTB as the matrix. The resulting LIFT spectra are indistinguishable. The alternative use of pencil lead is found inferior as a matrix but proves an exceptionally facile method of creating sodium and potassium adducts. The fragmentation of these metallated OCFs reveals different fragmentation pathways allowing the differentiation of the OCF isomers. This is evidently caused by the different interactions of the metal cation with the heteroatoms at the rim of the orifice. Additionally, the influence of the functionalization and isomer structure on the sodium ion affinity (SIA) is analysed by the kinetic method investigating the dissociations of sodium-bound hetero-dimers in electrospray ionization/ collision-induced dissociation (ESI-CID) experiments. (C) 2018 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2019-02-21